2011
DOI: 10.1007/s10734-011-9422-2
|View full text |Cite
|
Sign up to set email alerts
|

Access to postsecondary education: can schools compensate for socioeconomic disadvantage?

Abstract: While access to postsecondary education in Canada has increased over the past decade, a number of recent studies demonstrate that youth from disadvantaged socioeconomic backgrounds are vulnerable to some degree of exclusion from postsecondary education. These studies tend to emphasize the lack of financial resources and social capital as the main sources of this vulnerability. Our paper employs multilevel framework to explore the extent of the impact of schools on access to postsecondary education, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 7 publications
0
30
0
1
Order By: Relevance
“…The result is a range of analyses based on all 15-year old students from the sampled schools. In these analyses the implicit assumption is made that all students from one grade experience and contribute to the same class-level disciplinary climate (Frempong et al, 2012;OECD, 2005b;Olsen, 2003;Rangvid, 2003;Välijärvi, Kupari, & Linnakylä, 2007). Only Olsen (2003) addresses this issue by including the headmaster's view on the disciplinary climate in the school in his analysis and arguing for the presence of a school-specific disciplinary climate culture.…”
Section: Disciplinary Climate Student Achievement and Level Of Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is a range of analyses based on all 15-year old students from the sampled schools. In these analyses the implicit assumption is made that all students from one grade experience and contribute to the same class-level disciplinary climate (Frempong et al, 2012;OECD, 2005b;Olsen, 2003;Rangvid, 2003;Välijärvi, Kupari, & Linnakylä, 2007). Only Olsen (2003) addresses this issue by including the headmaster's view on the disciplinary climate in the school in his analysis and arguing for the presence of a school-specific disciplinary climate culture.…”
Section: Disciplinary Climate Student Achievement and Level Of Analysesmentioning
confidence: 99%
“…A multitude of studies report statistically significant as well as substantively important effects of classroom disciplinary climate on student achievement (Arum & Velez, 2012;Figlio, 2007;Frempong, Ma, & Mensah, 2012;Marks, 2010;Ning, Van Damme, Van Den Noortgate, Yang, & Gielen, 2015;Teodorović, 2011). Given the relevance of disciplinary climate for learning, some of the major international large scale assessment studies have incorporated measures for classroom climate in the student questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Applicants from schools with high concentrations of low SES students are less likely to go to university than similarly qualified students in other schools (Frempong et al 2011). The effects of coming from a school with a high percentage of free school meal recipients was found to be positively associated with degree performance after taking prior attainment into account (Crawford 2014b).…”
Section: % Pupils Eligible For Free School Mealsmentioning
confidence: 99%
“…Third, socio-economic background and parents' educational attainment also play a role in Germany in determining whether a student enters a bachelor's or master's programme (Orr et al, 2011). Students of lower socio-economic status are typically underrepresented in tertiary education (Powell and Solga, 2011;Frempong et al, 2012). A recent study showed that 50% of all students in Germany during the summer semester 2012 had a parent with a university degree (Middendorff et al, 2013).…”
Section: Cultural Factors Motivating Master's Degree Enrolmentmentioning
confidence: 99%